Stress-relieving properties of a polyherbal blend with Syzygium aromaticum L. and Coffea canephora Pierre ex A. Froehner: a review and bibliometric analysis - Zakaria, Nor Hafizah; Awang, Anis Fadhlina Izyani; Sheikh Mohamed, Hassan Ibrahim; Hairani, Muhammad Afnan Shakir; Mohd Fauzi, Mohd Syabil Haiman; Abdul Majid, Fadzilah Adibah (Taylor & Francis, 2024)
Objective: Syzygium aromaticum and Coffea canephora are acknowledged for their outstanding antioxidant, anti-inflammatory, and nerve-stimulant properties, showcasing potential in brain protection. Therefore, this study aims to quantitatively review existing literature and assess the potential of using it to formulate a herbal tea blend for managing stress and anxiety. Methods: Data was retrieved from the Scopus database, and a bibliometric analysis was performed using VOSviewer software. Results: Following a screening process, a total of 121 articles were identified, with S. aromaticum yielding a higher number compared to C. canephora. A detailed exploration of each plant revealed active components such as eugenol, β-caryophyllene, α-humulene, caffeine, mangiferin, and chlorogenic acids, each exhibiting stimulatory effects alongside antioxidant and anti-inflammatory properties. The neuroprotective effects were attributed to the reduction of oxidative stress and inflammation, coupled with the stimulation of neurotransmitters and hormones like dopamine, serotonin, cortisol, and adrenaline. Conclusions: The review showed that these plants positively affect mood and cognition by influencing the brain’s pleasure system. This suggests the need for further research to combine these plant extracts for developing ‘Tenang tea’, a potential herbal blend for managing stress and anxiety.